Efficacy according to blind independent central review: Post-hoc analyses from the phase III, randomized, multicenter, IPASS study of first-line gefitinib versus carboplatin/paclitaxel in Asian patients with EGFR mutation-positive advanced NSCLC. (February 2017) - Wu, Yi-Long; Saijo, Nagahiro; Thongprasert, Sumitra; Yang, J. C.-H.; Han, Baohui; Margono, Benjamin; Chewaskulyong, Busayamas; Sunpaweravong, Patrapim; Ohe, Yuichiro; Ichinose, Yukito; Yang, Jin-Ji; Mok, Tony S.K.; et al.
Highlights: IPASS: open-label study of first-line gefitinib vs carboplatin/paclitaxel in NSCLC. IPASS confirmed that EGFR mutation status predicted response to EGFR TKIs. Blind independent central review of IPASS outcomes was conducted (FDA request). Review of IPASS outcomes supported findings of the original investigators. EGFR TKI therapy is thus verified as standard-of-care in this first-line setting . . Abstract: Objective: The Phase III, randomized, open-label IPASS study (NCT00322452) of first-line epidermal growth factor receptor tyrosine kinase inhibitor (EGFR TKI) gefitinib versus carboplatin/paclitaxel for Asian patients with advanced non-small-cell lung cancer (NSCLC) showed that investigator-assessed progression-free survival (PFS) and objective response rate (ORR) were significantly prolonged in patients with EGFR mutation-positive NSCLC who received gefitinib versus patients with EGFR mutation-negative NSCLC. We report post-hoc analyses of IPASS data by blind independent central review (BICR), performed at the request of the US FDA, in a subset of patients with EGFR mutation-positive NSCLC. Patients and methods: Eligible patients (aged ≥18 years; histologically/cytologically confirmed Stage IIB/IV adenocarcinoma NSCLC; non- or former light-smokers; treatment-naïve) were randomly assigned 1:1 to gefitinib (250 mg/day) or carboplatin (dose calculated to produce an area under the curve of 5 or 6 mg/mL/minute)/paclitaxel (200 mg/m 2 ). Primary endpoint: PFS. BICR analyses included PFS, ORR, and duration of response (DoR). Results: Scans from 186 IPASS patients (gefitinib n = 88, carboplatin/paclitaxel n = 98) with EGFR mutation-positive NSCLC were available for BICR. Consistent with investigator-assessed results, in patients with EGFR mutation-positive NSCLC: PFS (hazard ratio 0.54; 95% confidence interval [CI] 0.38, 0.79; p = 0.0012) and ORR (odds ratio 3.00; 95% CI 1.63, 5.54; p = 0.0004) were significantly longer with gefitinib versus carboplatin/paclitaxel. The median DoR by BICR was 9.6 months with gefitinib and 5.5 months with carboplatin/paclitaxel. Conclusion: BICR analysis of IPASS data support the original, investigator-assessed results. EGFR mutation-positive status remains a significant predictor of response to first-line TKI therapy.